Leadership strategies for inclusive education systematic review: how school principals support special needs students - Nazmin Abdullah; Surianti Lajuma; Mohd Fairuz Jafar; Mohd Nadzri Ishak; Siti Suriati Khairon (Intelektual Pustaka Media Utama, 2026)
This article examines the leadership strategies used by school principals to manage inclusive education for students with special educational needs. Based on a systematic review of 25 articles from top academic journals (2021-2025), the research highlights the key role principals play in promoting inclusivity in schools. Findings show that effective leadership practices, such as transformational leadership, community involvement, and resource allocation, significantly enhance the success of inclusive education. Principals who foster a culture of support and high expectations for teachers contribute to better educational outcomes for special educational needs students. The study also emphasizes the importance of collaboration between teachers, parents, and external organizations in supporting inclusive practices. However, the research identifies challenges that principals face, such as limited resources and managing diverse learning needs. Professional development and ongoing training for educators are crucial for overcoming these barriers. The article concludes that while character-driven leadership centered on integrity, empathy, and ethical decision-making plays a positive role in building an inclusive school environment, it must be balanced with practical strategies to address operational challenges. Effective leadership is essential for creating a sustainable, inclusive educational environment that meets the diverse needs of all students.